Global faith and worldly power: evangelical internationalism and U.S. empire - Corrigan, John; McAlister, Melani; Schäfer, Axel R. (The University of North Carolina Press, 2022)
"Assessing the grand American evangelical missionary venture to convert the world, this international group of leading scholars reveals how theological imperatives have intersected with worldly imaginaries from the nineteenth century to the present. Countering the stubborn notion that conservative Protestant groups have steadfastly maintained their distance from governmental and economic affairs, these experts show how believers' ambitious investments in missionizing and humanitarianism have connected with worldly matters of empire, the Cold War, foreign policy, and neoliberalism"--